The Impact of Big Five Personality towards Impulsive Buying Behavior - Firda Deviyana Rizki; Arianis Chan; Cecep Safa’atul Barkah; Pratami Wulan Tresna (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: This research aims to determine which type of The Big Five Personality impacted the impulsive buying behavior of TnT Rajut’s customers. Design/methodology/approach: This research proposes two strategies based on TnT Rajut’s SWOT analysis, social media activation and bundling price strategy. Findings: Based on the calculated data from respondents, it is shown that Openness to Experience, Extraversion, and Agreeableness impacted the impulsive buying behavior. Research limitations/implications: Meanwhile, Conscientiousness and Neuroticism didn’t impact impulsive buying behavior. Originality/value: This paper is original Paper type: Research Paper